Legal Review of Justice Collaborator in The Concept of Criminal Law - Dadin Eka Saputra (LAFADZ JAYA Publisher, 2023)
The existence of a justice collaborator is very important to uncover organized crime cases. However, in terms of its regulation regarding certain aspects of a person, it does not reflect legal certainty. In this regard, the purpose of this study is to analyze the determination of a person's legal status as a justice collaborator and the role of the LPSK in protecting justice collaborators. This research uses normative legal research, namely research on secondary data in the form of primary, secondary, and tertiary legal materials. These legal materials are collected using literature studies, then processed and analyzed in a qualitative descriptive manner. The results showed that the determination of the legal status of the justice collaborator at the time of investigation and definitively carried out by the judge at the court hearing. Then the role of the LPSK in protecting justice collaborators from the fulfilment of the requirements until the process of handling criminal cases has permanent legal force.